PENGARUH IMPLEMENTASI SISTEM SIM ONLINE TERHADAP PENINGKATAN KINERJA ANGGOTA DI POLRESTA SURAKARTA DENGAN KEPUASAN MASYARAKAT SEBAGAI VARIABEL MEDIASI - Suprayitno, Sutiman & (Universitas Slamet Riyadi, 2017)
This research aims to analyses (1) significance effect implementation ofthe SIM-online system on public satisfaction (2) significance effectimplementation of the SIM-online system on performance of the policemembers (3) significance effect public satisfaction on performance of thepolice members (4) the effect implementation of the SIM-online system onperformance of the police members mediated public satisfaction. Location ofthis research in Surakarta regency police department, using samples of 100communities who using services of SIM-online system with accidentalsampling technique. Data collecting with questionnaire technique throughvalidity and reliability test. To test hypothesis using path analysis. The resultshows that (1) implementation of the SIM-online system has significanceeffect on public satisfaction, so the hypothesis 1 accepted; (2)implementation of the SIM-online system has significance effect onperformance of the police members, so the hypothesis 2 accepted; (3) publicsatisfaction has significance effect on performance of the police members, sothe hypothesis 3 accepted; (4) the effect implementation of the SIM-onlinesystem on performance of the police members mediated public satisfaction,so the hypothesis 4 accepted.Keywords: implementation of the SIM-online system, public satisfaction,performance of the police members